Green Accounting, Corporate Social Responsibility, and Firm Value in Indonesian Coal Mining - Efrilawati Efrilawati; Evi Yuniarti; Rusmianto Rusmianto (Goodwood Publishing, 2026)
Purpose: This study examines the effects of green accounting and Corporate Social Responsibility (CSR) disclosure on firm value, while controlling for firm size, among Indonesian coal mining companies listed on the Indonesia Stock Exchange from 2021 to 2024.Methodology: This study uses a quantitative pooled firm-year design based on annual, financial, and sustainability reports. Purposive sampling produced 23 companies and 92 firm-year observations; after outlier treatment, the final regression used 84 observations. Descriptive statistics, classical assumption tests, multiple linear regression, t-tests, an F-test, and adjusted R-squared were estimated using IBM SPSS Statistics (version 25).Results: Green accounting had were positively and significantly associated with firm value (B = 2.334; β = 0.424; p < 0.001), as did CSR disclosure (B = 0.534; β = 0.221; p = 0.028, respectively). Firm size was also positively significant (B = 1.894; p = 0.004). The model was significant (F = 9.703; p < 0.001) and explained 23.2% of the variation in the firm value.Conclusions: Environmental expenditure and broader CSR disclosure are value-relevant signals in Indonesia’s coal mining sector, even when company scale is considered.Limitations: The study is limited to one sector, a four-year period, pooled regression, and disclosure-based measures that do not assess the program quality.Contributions: The findings extend the sustainability accounting evidence and inform managers and investors about the market relevance of environmental and social disclosures.Novelty: This study jointly tests environmental expenditure and GRI-based CSR disclosure in a high-exposure industry while explicitly controlling for firm size.